NOVELTIES IN BRAZILIAN BEGONIACEAE II: a new species from Minas Gerais - Kollmann, Ludovic Jean Charles (Phytotaxa, 2020)
Begonia vasconselosiana, a new species of Begonia from Minas Gerais state, Brazil is described. Begonia vasconselosiana is morphologically similar to Begonia lealii Brade with which it is compared. The new species grows in campos rupestres in Atlantic Forest, east of Minas Gerais state, Brazil. Description, diagnosis, etymology, taxonomic comments, illustrations, and conservation status of the new species are provided.